Visibility, Preservation and Colour: A Descriptive System for the Study of Opal Phytoliths in (Archaeological) Soil and Sediment Thin Sections. (2nd April 2020) - Vrydaghs, Luc; Devos, Yannick
ABSTRACT: Phytoliths are abundantly reported in (archaeological) soil thin sections. However, standard description systems are largely missing. The purpose of this paper is to present a descriptive system describing three aspects of phytoliths in soil thin sections: visibility, preservation and colour (VPC). The visibility expresses to which extent the phytoliths are masked or surrounded by fine material. The preservation is an indicator for the physico-chemical alterations that affected the phytoliths. Finally, colour is an indicator of the charring of the organic material surrounding the phytoliths.